Application the storytelling method of the knowledge management for the constitution organizational memory of Shindo Renmei Movement - Kajimoto, Natacha; Pomim Valentim, Marta Ligia [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2017)
Introduction: The first relations between Brazil and Japan occurred in the last decade of the Nineteenth Century. In Brazil, Japanese immigration began in 1908 with the arrival of the ship Kasato-Maru. With the beginning of World War II, there was an interruption in the immigration cycle, a result of the attacks on Hiroshima and Nagasaki and Japan's surrender to the United States. In Brazil, the immigrants did not accept the fact that Japan had lost the war, and thus were divided into two groups Kachigumi [victorious] and Makegumi [defeated]. The Shindo Renmei Movement was formed by those who called themselves Kachigumi which, in turn, killed and destroyed the establishments of Japanese who admitted the defeat of Japan to the United States. Objective: Reconstruct part of the memory of Movement Shindo Renmei more specifically related to Marilia, Sao Paulo State. Method: Relying on knowledge management, whose methods enable the conversion of tacit knowledge to explicit knowledge, we used the method called Storytelling with the goal of getting reports from people who participated and experienced the Shindo Renmei Movement in Marlia, to facilitate the rescue of part of the memory that organization. Results: The study afforded comprehension of the relevance to rescue the organizational memory, in this case the Shindo Renmei Movement as a formal organization that was established with well-defined objectives and proved the viability of applying the Storytelling method of management knowledge to the rescue of memories of this type.
Keywords: Japanese Immigration; Knowledge Management; Marilia (Sao Paulo, Brazil); Organizational Memory; Shindo Renmei Movement; Storytelling Method